Synthesis of Novel 1,2,4-Triazolyl Coumarin Derivatives as Potential Anticancer Agents - Lamya H. Al-Wahaibi; Hanaa M. Abu-Melha; Diaa A. Ibrahim (Journal of Chemistry)
A series of novel coumarin derivatives carrying 1,2,4-triazole or 1,2,4-triazolo[3,4-b][1,3,4]thiadiazole moieties were prepared and evaluated in vitro as anticancer in the human colon cancer (HCT116) cell line. The derivatives 4c and 8c exhibited marked anticancer activity with IC50 values 4.363 and 2.656 µM, respectively. The molecular docking studies suggested possible interaction with tyrosine kinases (CDK2).